Missionary expatriate effectiveness : how personality, calling, and learned competencies influence the expatriate transitions of Pentecostal missionaries - Plake, John Farquhar. (Global Pentecostal and Charismatic Studies, 2016)
In Missionary Expatriate Effectiveness , John Farquhar Plake examines how Pentecostal missionaries adjust to foreign cultural environments and become proficient at their work abroad. Connecting the disciplines of psychology, human resource management, and missiology, Plake provides unique insights into the predictors of expatriate effectiveness through the experience of 949 missionaries working in 127 nations. Responding to the question, "Are missionaries born, called, or made?", Plake provides evidence that cross-cultural training is a critical component of missionary formation. Here missionaries, educators, mission agency leaders, I-O psychologists, and cross-cultural scholars will find actionable data and a hopeful, nuanced picture of reality, grounded in the lived experiences of Pentecostal missionaries worldwide.